ENHANCING THE PRODUCTIVITY OF CHICKPEA THROUGH FOLIAR NUTRITION UNDER RAINFED CONDITIONS - M. RATNAM*, D. SOWMYA and G. KISHORE BABU, (The Journal of Research ANGRAU, 2024)
The study was carried out at Regional Agricultural Research Station, Lam for three years (2020-21, 2021-22, 2022-23) for assessing the productivity of chickpea using foliar nutrition under rainfed conditions of the Krishna Agro Climatic Zone of South Coastal Andhra Pradesh. The experiment was laid out in Randomized Block Design and was replicated thrice. The experiment consisting of eight treatments viz., control (RDF:N20:P50:K0 kg ha -1), application of water soluble NPK, Zn, Fe, soluble monophosphate and soluble potassium nitrate at different stages alone and in combinations. Pooled analysis (2020-2023) of the experimental results revealed that along with recommended dose of fertilizers (N20:P50:K0 kg ha-1) foliar application of Zn @ 0.2% at pre flowering, water soluble monophosphate @1% at flowering and water soluble potassium nitrate @1% at pod filling stage recorded significantly higher seed yield (1871 kg ha-1) and protein content (22.90%) which was on par with foliar application of Fe @ 0.5% at pre flowering, monophosphate@1% at flowering and potassium nitrate @ 1% at pod filling stage with seed yield (1821 kg ha -1) and (22.63%) protein content, both the treatments recorded BCR of 1.9.